Regulation of C-Type Lectin Receptor-Mediated Antifungal Immunity - Tang, Juan; Lin, Guoxin; Langdon, Wallace Y.; Tao, Lijian; Zhang, Jian (Frontiers in Immunology, 2018)
Of all the pathogen recognition receptor (PRR) families, C-type lectin receptor (CLR)-induced intracellular signal cascades are indispensable for the initiation and regulation of anti-fungal immunity. Ongoing experiments over the last decade have elicited diverse CLR functions and novel regulatory mechanisms of CLR-mediated signaling pathways. In this review, we highlight novel insights in anti-fungal innate and adaptive protective immunity mediated by CLRs, and discuss the potential therapeutic strategies against fungal infection based on targeting the mediators in the host immune system.